PELATIHAN PEMBUATAN PAKAN AYAM BROILER DENGAN MEMANFAATKAN BAHAN PAKAN LOKAL DI KOTA TERNATE - Nur Sjafani; M Ade Salim (Bajang Institute, 2022)
Community service activities aim to improve the skills of group members in making broiler chicken feed in order to overcome the increasing price of feed. The solutions offered are through several methods, namely 1) approaching by discussing the problems faced by partner groups, 2) counseling and training for partner groups in Jan Village, South Ternate District. The results of the service activities of group members know the types of local materials and agricultural waste that can be used as a mixture of broiler chicken feed. Partners know and have been able to make feed from several local feed ingredients that are available for broilers with different growth phases. The results of observations showed that broiler chickens given a mixture of local feed ingredients showed good performance and farmers did not use antibiotics in their maintenance.